2019
DOI: 10.1016/j.ijwd.2019.06.030
|View full text |Cite
|
Sign up to set email alerts
|

Skin disease related to metabolic syndrome in women

Abstract: Sex hormones are involved in pathways of metabolic syndrome (MetS), an observation supported by animal studies. The relationships of sex hormones with components of MetS, such as insulin resistance and dyslipidemia, have been studied in pre- and postmenopausal women. High testosterone, low sex hormone-binding globulin, and low estrogen levels increase the risks of MetS and type 2 diabetes in women. Cutaneous diseases that are sex hormone mediated, such as polycystic ovary syndrome, acanthosis nigricans, acne v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
11
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 160 publications
(189 reference statements)
2
11
0
12
Order By: Relevance
“…8 Given that psoriasis is a chronic inflammatory disease, it poses a greater risk of CVD in women. 9 This study 5 showed higher prevalence of metabolic syndrome in cases with psoriasis than in controls, which is in accordance with the research conducted by Regitz-Zagrosek et al 8,9 It has been concluded in a study done by Pietrzak et al 10 that the relation of CVD and psoriasis in females intensifies with age. However, no such associations have been recorded in this study.…”
supporting
confidence: 89%
“…8 Given that psoriasis is a chronic inflammatory disease, it poses a greater risk of CVD in women. 9 This study 5 showed higher prevalence of metabolic syndrome in cases with psoriasis than in controls, which is in accordance with the research conducted by Regitz-Zagrosek et al 8,9 It has been concluded in a study done by Pietrzak et al 10 that the relation of CVD and psoriasis in females intensifies with age. However, no such associations have been recorded in this study.…”
supporting
confidence: 89%
“…High testosterone, low sex hormone-binding globulin (SHBG), and low estrogen levels increase the risks of MetSyn and T2DM in women. In this study, several diseases mediated by sex hormones, including PCOS, acanthosis nigricans, acne vulgaris, and pattern alopecia, were associated with IR and increased risk for MetSyn [55]. Furthermore, Weeker et al…”
Section: Indicators Related To Associated Diseases/syndromessupporting
confidence: 51%
“…Androgens (Testosterone) and SHBG: Men with low concentrations of total testosterone (TT), SHBG, or free testosterone (FT) were more likely to have prevalent MetSyn (ORs per quartile decrease were 1.69 (95%CI: 1.60e1.77), 1.73 (95%CI: 1.62e1.85), and 1.46 (95%CI: 1.36e1.57) for TT, SHBG, and FT, respectively) and incident MetSyn [85]. This association was also observed in women (not in a meta-analysis) [55]. In perimenopausal and postmenopausal women, androgenic markers (testosterone and SHBG) are more important than estrogens in the assessment of MetSyn.…”
Section: Indicators Related To Blood Biomarkersmentioning
confidence: 87%
“…Finally, acanthosis nigricans and skin tags were much more prevalent in Keen et al’s report, at 30% and 9%, respectively [ 10 ], than in our sample. This difference may be attributed to differences in our samples’ fasting blood glucose and fasting insulin levels, which serve as reflections of insulin resistance, the pathophysiology responsible for acanthosis nigricans and skin tags [ 23 ].…”
Section: Discussionmentioning
confidence: 99%